Equity through innovation in teaching and learning: A student‐centered approach to systemwide implementation of direct assessment CBE. Issue 1 (30th March 2021) - Lowe, Aisha; Leal‐Carrillo, Nadia; Guiney, Chantee; Diaz, Amparo
Abstract: The California Community Colleges (CCC) system has adopted an equity‐imperative approach to systemic reforms. As part of this effort, and to meet the state's workforce demands of the future, the system has focused on better serving the needs of adult learners, those between the ages of 25 and 64 with some college but no degree. The current impact of COVID‐19 has exacerbated the inequitable learning experiences of minoritized students and has forced the system to reimagine teaching and learning, with urgency. With a heightened focus on access, persistence, and the success of CCC students, direct assessment competency‐based education (CBE) through self‐paced learning, high‐touch and high‐tech student support is a clear next step in the evolution of teaching and learning to meet the needs of adult learners. This paper discusses the impetus for such innovation and the CCC system's effort to add direct assessment CBE to its educational offerings.